Prevalence of Color Vision Deficiencies - I. A. Makarov (Oftalʹmologiâ, 2020)
Purpose. The study of color deficiencies prevalence in young people, students of higher educational university.Materials and methods. The study was carried for the half year — fall semester. A total of 1,609 students were examined, aged 17–21. There were 1191 boys and 418 girls. The survey was conducted to determine the health groups in physical training and in various sports sections. An ophthalmologic examination determined refractive disorders and other ocular pathology, which is important for determining health groups. Rabkin polychromatic tables and Neitz color vision test (Neitz Lab (UW Medicine) were used for determining of color deficiencies. The obtained results of these tests were compared in terms of the time spent on the test, the results of the test effectiveness, the determination of dissimulation, and the assessment of the shift in the color spectrum in individuals with impaired color perception.Results. A total of refractive disorders were detected in 856 students (53.2 %). The high degree of myopia was in 40. Disorders of color deficient were noted in 101 students (8.48 %) of 1191 male subjects when using the Neitz color test. Dichromatic eye changes were observed from 2.1 % students: protanopia and deiteranopia were in 0.67 % and 1.43 %. Most of all there were violations with the perception of shades of light brown and light green colors. A third of healthy students noted the impossibility of distinguishing light brown from light gray. This is regardless of the state of refraction. Simultaneous violations of the perception of shades of red, green, yellow and blue were observed in one subject, it was associated with congenital cataracts. In four young people, acquired eye diseases caused. In two girls, violations of the perception of a pastel shade of light green were noted, with one girl (0.24 %) having a violation in two eyes, and was presumably due to a gene anomaly. The second girl had one eye and was associated with partial atrophy of the optic nerve after the optic neuritis.Conclusions. Neitz color test expands the diagnostic possibilities, since in its design it has pastel shades of light green and light brown colors on a gray background, reduces the likelihood of dissimulation, reduces the time of the survey. Neitz color test allows to expand the possibilities for more accurate and differential diagnosis dichromatic and anormal trichromatic subjects and acquired color vision defects.